2012
DOI: 10.3233/wor-2012-1006-406
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of physical workload in boiler operations

Abstract: The use of boiler wood-fired is fairly common equipment utilized in steam generation for energy production in small industries. The boiler activities are considered dangerous and heavy, mainly due to risks of explosions and the lack of mechanization of the process. This study assessed the burden of physical labor that operators of boilers are subjected during the workday. Assessment of these conditions was carried out through quantitative and qualitative measurements. A heart rate monitor, a wet-bulb globe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
1
0
3
Order By: Relevance
“…In recent years, SB intervention in the workplace has attracted wide attention in the field of public health. Two recent systemic reviews [8,9] reported that majority of the interventions have mainly focused on decreasing the prolonged sitting time by breaking sitting with periodic prompts [10][11][12], promoting changes in sitting position with sit-stand workstations [13][14][15][16][17][18][19][20], and combining work with low-intensity physical activity (e.g., treadmill working station).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, SB intervention in the workplace has attracted wide attention in the field of public health. Two recent systemic reviews [8,9] reported that majority of the interventions have mainly focused on decreasing the prolonged sitting time by breaking sitting with periodic prompts [10][11][12], promoting changes in sitting position with sit-stand workstations [13][14][15][16][17][18][19][20], and combining work with low-intensity physical activity (e.g., treadmill working station).…”
Section: Introductionmentioning
confidence: 99%
“…Para trabajos en altas temperaturas, el incremento en el ritmo cardiaco se presenta como consecuencia del intercambio de calor entre el cuerpo y el ambiente; en estos casos se incrementa el bombeo de sangre para mantener la temperatura corporal (cercana a los 37ºC) y para garantizar el funcionamiento de los músculos involucrados en la actividad. El monitoreo del ritmo cardiaco usualmente es realizado con un sensor transmisor que es colocado en el pecho de la persona y un dispositivo receptor que recibe las señales (Rodrigues, 2012).…”
Section: Métodos De Medición De Consumo Energético a Través De Variab...unclassified
“…A partir de ese momento comienza a descender hasta los valores en reposo (Instituto nacional de seguridad e higiene en el trabajo, 2014). Esta herramienta permite evidenciar si existe algún efecto dada la exposición a calor, ya que el ritmo cardiaco puede presentar cambios cuando el cuerpo se encuentra a un ambiente de alta temperatura, en estas situaciones, el corazón eleva el bombeo de sangre para mantener la temperatura del cuerpo alrededor de los 37°C y garantizar el suministro se sangre a los músculos durante la actividad (Rodrigues, 2012).…”
Section: Consumo Energético a Través De Variables Fisiológicasunclassified
See 1 more Smart Citation